Early childbearing experiences of young university student‐parents in South Africa: A qualitative study - Seluleko Eric Ngcobo; Kemist Shumba (Wiley, 2023)
Abstract Background Early childbearing is a major concern especially in developing countries. This study sought to understand student‐parents' perspectives of early childbearing, describe their individual experiences and identify the types of support required for such young parents. Methods This was an exploratory qualitative study with semi‐structured in‐depth interviews among 20 purposively selected participants. All the participants were young parent‐students at the University of KwaZulu‐Natal in Durban, South Africa. The interviews were conducted in 2018. Results The young parent‐students identified a lack of adequate information and knowledge about safe sex, contraceptive methods and prevention of pregnancies that led to early childbearing. The common misinformation that prevented the adoption of contraception methods were societal beliefs among men promoting early childbearing, coupled with the negative attitudes of healthcare workers in providing adequate information and reproductive health services. Both male and female parents suffered life‐changing consequences after early childbearing leading to financial burdens to support their new‐born and the interruption of their education. Government financial schemes and bursaries helped these young parents to financially support their new‐born, whereas family support in terms of taking care of the new‐born allowed them to continue with education. In addition, most participants identified having a child as a motivation for pursuing higher education. There is a need for Life Orientation programmes to be tailor‐made to provide adequate knowledge and sensitise the youth on appropriate life choices and access to contraceptives. Conclusion Early childbearing resulted from a lack of adequate knowledge on safe sex and contraceptive methods, poor access to contraceptives, the negative attitudes of healthcare workers in proving adequate sexual and reproductive health services to the youth. Schemes to financially support the young parents and support from family members were key to helping the young parents to continue with university education.